Assessment of knowledge and awareness about biomedical waste management among health care personnel in a tertiary care dental facility in Delhi - Meera Choudhary; Mahesh Verma; Sujoy Ghosh; Jatinder Kaur Dhillon (Wolters Kluwer Medknow Publications, 2020)
Aim: The study was conducted to assess knowledge and awareness of biomedical waste management (BMWM) among undergraduate students, residents, and nursing staff in a tertiary care dental facility in Delhi. Materials and Methods: A questionnaire survey (using ten close ended questions) was conducted regarding various aspects of BMWM among undergraduate students, residents, and nursing staff in a tertiary care dental facility. In each group, scores were determined depending upon the correct responses, the participants marked. The data were compiled and subjected to statistical analysis. Results: Only 33.3% undergraduate students gave over 70% correct answers as compared to nursing staff (100%) and residents (62.2%). Undergraduate students showed various lacunae in terms of knowledge regarding BMWM. The difference between the knowledge of the 3 groups i.e., nursing staff, residents, and undergraduate students was statistically significant (P = 0.001). Residents exhibited better awareness regarding BMWM as compared to undergraduate students (P = 0.003). Conclusion: The pertinence of the issue of BMWM and lack of adequate preparation of the trainee dentists at undergraduate level reflects the urgent need to fill the lacunae in the dental undergraduate curriculum.